PRAKTIK AL-ISTISQAAQ DALAM ISLAM - Khairillina (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2020)
Al-Istihqaaq is a person who sues and claims ownership of something, then it isclaimed and the lawsuit can be proven and the judge wins the suit. If mustahiqproves that the goods sold are his property not the property of the seller, then thejudge wins the claim and claim, then the sale and purchase of the existing aqaddoes not necessarily become null and void, but is deferred to the permission andapproval of mustahiqq. There are two aqad in al-istisqaaq namely: aqad buyingand selling al-muqaaiyadhah (barter). Al-istihqaaq happened in ar-rahn, meaningthat the pawned goods turned out to be the property of others, not the rights of arraahin(who mortgaged) themselves. Uluma agreed to declare in theimplementation of al-Istihqaaq may not contain elements that can damage thecontract and there is tyranny.